2021
DOI: 10.3390/ijms22158016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Use of the sGC Stimulator BAY-747, as a Potential Treatment for Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a severe and progressive muscle wasting disorder, affecting one in 3500 to 5000 boys worldwide. The NO-sGC-cGMP pathway plays an important role in skeletal muscle function, primarily by improving blood flow and oxygen supply to the muscles during exercise. In fact, PDE5 inhibitors have previously been investigated as a potential therapy for DMD, however, a large-scale Phase III clinical trial did not meet its primary endpoint. Since the efficacy of PDE5i is dependent on suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the Special Issue, the manuscript by Krishnan et al reports a potential further treatment option for sGC modulation in the context of Duchenne Muscular Dystrophy (DMD). The sGC stimulator BAY-747 improved several functional and pathological parameters of skeletal muscle in the DMD murine model, which suggests a possible application of sGC modulators in this disease [ 3 ].…”
Section: Communicationmentioning
confidence: 99%
“…In the Special Issue, the manuscript by Krishnan et al reports a potential further treatment option for sGC modulation in the context of Duchenne Muscular Dystrophy (DMD). The sGC stimulator BAY-747 improved several functional and pathological parameters of skeletal muscle in the DMD murine model, which suggests a possible application of sGC modulators in this disease [ 3 ].…”
Section: Communicationmentioning
confidence: 99%
“…For skeletal muscle, sGC stimulation can increase the oxygen transport and improve exercise efficiency. In addition, sGC can also modulate muscle microtubule organization and mitochondrial oxidative phosphorylation ultimately improving muscle fatigue ( Krishnan et al, 2021 ). A recent research reported sGC as a potential therapeutic target in DOX-induced heart failure ( Todorova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%